2005
DOI: 10.2111/1551-5028(2005)58[299:fssyaq]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Fourwing Saltbush Seed Yield and Quality: Irrigation, Fertilization, and Ecotype Effects

Abstract: Clones of superior pollen-and seed-producing plants of 4 fourwing saltbush (Atriplex canescens [Pursh] Nutt.) ecotypes were planted in a seed orchard in west-central Texas to determine if seed production and quality could be enhanced by irrigation and fertilization. Subplots of nitrogen (N) at 112 kg~ha À1 , phosphorous (P) at 112 kg~ha À1 , N þ P at 112 þ 112 kg~ha À1 , or no fertilizer were superimposed on irrigated or dryland main-plots. Neither irrigation nor fertilization affected estimated seed yields or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…There are few published studies examining seed production of native plants in response to irrigation in arid regions. In a westcentral Texas, area that receives 530 mm of annual precipitation, Petersen and Ueckert (2005) found that seed production of Atriplex canescens (fourwing saltbush) did not respond to either 400 mm of irrigation in one year or 200 mm of irrigation the next year. In the Owens Valley, CA, with annual precipitation of 113 mm, Sarcobatus vermiculatus (greasewood) seed yields were significantly higher when irrigated (Breen and Richards, 2008).…”
Section: Discussionmentioning
confidence: 97%
“…There are few published studies examining seed production of native plants in response to irrigation in arid regions. In a westcentral Texas, area that receives 530 mm of annual precipitation, Petersen and Ueckert (2005) found that seed production of Atriplex canescens (fourwing saltbush) did not respond to either 400 mm of irrigation in one year or 200 mm of irrigation the next year. In the Owens Valley, CA, with annual precipitation of 113 mm, Sarcobatus vermiculatus (greasewood) seed yields were significantly higher when irrigated (Breen and Richards, 2008).…”
Section: Discussionmentioning
confidence: 97%
“…Nonetheless, advances in our understanding of reproductive allometry suggest that measures of plant size offer a robust estimate of seed production in many species (Niklas 1993;Niklas and Enquist 2003). Seed production is proportional to size of perennial plants (Hendriks and Mulder 2008;Shipley and Dion 1992), even for taxa found in this Mojave Desert system (Cleary et al 2008;Petersen and Ueckert 2005). Thus, plant size can be used to estimate available resources.…”
Section: Methodsmentioning
confidence: 99%
“…Irrigation amounts were 0, 100, and 200 mm. For the quadratic equations, the amount of irrigation that resulted in maximum yield was calculated using the formula x = -b/2c, where b is the linear parameter and c is the quadratic parameter, precipitation, Petersen and Ueckert (2005) found that seed production of Atriplex canescens (Pursh) Nutt. (fourwing saltbush) did not respond to either 400 mm of irrigation in 1 year or 200 mm of irrigation the next year.…”
Section: Discussionmentioning
confidence: 99%